Salivary human beta-defensins and cathelicidin levels in relation to periodontitis and type 2 diabetes mellitus - Dogukan Yilmaz; Ali Orkun Topcu; Emine Ulku Akcay; Mustafa Altındis; Ulvi Kahraman Gursoy (Taylor & Francis, 2022)
Objective: Type 2 diabetes mellitus (T2DM) is a well-defined risk factor of periodontitis and it can affect expression of human beta-defensins (hBDs) and cathelicidin (LL-37) as well. The aim of the present study was to evaluate the impact of periodontitis and T2DM on salivary concentrations of these antimicrobial peptides.
Material and methods: Unstimulated saliva samples, together with full-mouth periodontal recordings were collected from 92 individuals with periodontitis (63 with T2DM and 21 smokers) and 86 periodontally healthy controls (58 with T2DM and 21 smokers). Salivary hBD-1, -2, -3, LL-37, and advanced glycalization end products (AGE) concentrations were measured by enzyme-linked immunosorbent assay.
Results: Among the periodontitis patients, T2DM group demonstrated lower levels of hBD-1 (p = .006), hBD-2 (p < .001) and hBD-3 (p < .001), and higher levels of LL-37 (p < .001) compared to systemically healthy controls. When only periodontally healthy controls were included into the analysis, higher hBD-1 (p = .002) and LL-37 (p < .001) levels were found in T2DM patients in comparison to systemically healthy controls. Salivary LL-37 levels were associated with HbA1c and periodontitis, while hBD-2, hBD-3 and levels associated only with HbA1c.
Conclusion: In the limits of this study, hyperglycaemia can be proposed as a regulator of salivary hBD and cathelicidin levels. Periodontitis, on the other hand, affects only salivary LL-37 levels.